2017
DOI: 10.1101/130138
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genomic relatedness strengthens genetic connectedness across management units

Abstract: Genetic connectedness refers to a measure of genetic relatedness across management units (e.g., herds and flocks). With the presence of high genetic connectedness in management units, best linear unbiased prediction (BLUP) is known to provide reliable comparisons between genetic values. Genetic connectedness has been studied for pedigree-based BLUP; however, relatively little attention has been paid to using genomic information to measure connectedness. In this study, we assessed genome-based connectedness acr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 32 publications
1
23
0
Order By: Relevance
“…These results are in agreement with previous studies in pigs (Silva et al 2014) and cattle (Mota et al 2016). According to Forni et al (2011) and Yu et al (2017), using the H matrix instead of the A matrix for genetic evaluation will reduce the error of prediction owing to the better estimation of the kinship coefficient.…”
Section: (Co)variance Componentsmentioning
confidence: 99%
“…These results are in agreement with previous studies in pigs (Silva et al 2014) and cattle (Mota et al 2016). According to Forni et al (2011) and Yu et al (2017), using the H matrix instead of the A matrix for genetic evaluation will reduce the error of prediction owing to the better estimation of the kinship coefficient.…”
Section: (Co)variance Componentsmentioning
confidence: 99%
“…A CD metric measures the precision of genetic values and can be interpreted as the square of the correlation between the predicted and the true difference in the genetic values or the ratio of posterior and prior variances of genetic values u [10]. A notable difference between CD and PEVD is that CD penalizes connectedness measurements when across units include individuals that are genetically too similar [4,5]. A pairwise CD between individuals i and j is given by the following equation.…”
Section: Coefficient Of Determination (Cd)mentioning
confidence: 99%
“…This summary method for r statistic was used in Yu et al [4] and calculation steps are shown in Figure 4A.…”
Section: Prediction Error Correlation (R)mentioning
confidence: 99%
See 2 more Smart Citations